Pencurian dengan Pemberatan yang Dilakukan Anak Belum Dewasa: Studi Kasus Putusan No. 41/Pid.Sus-Anak/2020/PN.Plg - Dwi Badru Abdillah; Rusdiyanto Rusdiyanto (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
One of the crimes that has been formulated in the Criminal Code or a crime called "Theft with Aggravation" is regulated in Article 363 paragraph (1) 5th of the Criminal Code in conjunction with Article 25 in conjunction with Article 26 paragraph (1) of Law Number 3 of 1997 concerning Juvenile Justice , Aggravated theft committed by a child is a criminal offense. The specificity of this type of criminal act lies in the perpetrator/subject of the crime, namely children who are classified as minors who still have a long future as the nation's next generation. The aim of the criminal justice process is not punishment, but improving the condition, maintenance and protection of children as well as preventing and overcoming their actions through constructive court action. As related to the case of aggravated theft committed by a minor in case Number: 41/Pid.Sus-Anak/2020/PN.Plg. The method in this research is a normative juridical method or library research, namely research by analyzing applicable legal norms, both in the form of laws and court decisions. Research data was obtained from library materials and legal documentation in the form of primary, secondary and tertiary law. Then the data is collected by investing in statutory regulations, books and literature related to the research material. Finally, the existing data is then analyzed qualitatively, namely carrying out analysis without using numbers or formulas. The results of the research show that firstly, in the process of resolving criminal acts committed by immature children, in the examination process both at the investigation level and in the trial process, the children have been accompanied by community counselors (BISPA), parents, and Advocates/Legal Advisors. Second, the punishment of children who committed the crime of theft with aggravation in Case No. 41/Pid.Sus-Anak/2020/PN. Plg, it is regulated in Article 363 paragraph (1) 4th of the Criminal Code. This is based on legal facts that have been revealed in the trial, both from the testimony of the victim and witnesses as well as from the defendant's confession.